Feasibility, Safety, and Provider Perspectives of Bipolar Electrosurgical Cautery Device for (Opportunistic or Complete) Salpingectomy at the Time of Cesarean Delivery - Ostby, Stuart A.; Blanchard, Christina T.; Sanjanwala, Aalok R.; Szychowski, Jeff M.; Leath, Charles A., III; Huh, Warner K.; Subramaniam, Akila (American Journal of Perinatology, 2022)
Objective The aim of the study is to evaluate the use of a bipolar electrocautery device for complete salpingectomy at cesarean to improve procedure completion rates, operative time, and surgeon reported satisfaction as compared with standard bilateral tubal ligation (BTL) and suture-cut-tie salpingectomy.Study Design This is a prospective cohort study of women undergoing planned, non-emergent cesarean with desired sterilization with complete salpingectomy utilizing a bipolar electrocautery device. Study patients were compared with historic controls from a randomized controlled trial (RCT) of complete salpingectomy via suture-cut-tie method versus BTL conducted at our institution (SCORE trial, NCT02374827). Outcomes were compared with groups from the original RCT.Results Thirty-nine women were consecutively enrolled (12/2018–11/2019) into the device arm of the study and compared with the original SCORE cohort (n = 40 BTL, n = 40 salpingectomy without a device). Salpingectomy performance with the bipolar electrocautery device was successfully completed in 100% (39/39) of enrolled women, with one device failure requiring the use of a second device, as compared with 95% (38/40) in the BTL (p = 0.49) and 67.5% (27/40) in salpingectomies without a device (p < 0.001). Mean operative time of sterilization procedure alone demonstrated device use as having the shortest operative time of all (device salpingectomy 5.0 ± 3.6 vs. no device 18.5 ± 8.3 minutes, p < 0.001; and vs. BTL 6.9 ± 5.0, p = 0.032). Mean sterilization procedure endoscopic band ligation (EBL) was demonstrated to be significantly different between each group, least amongst BTL followed by device (6.3 ± 4.8 vs. 8.4 ± 24.8, p < 0.001), and most by suture-cut-tie method (17.7 ± 14.3, p < 0.001 compared with device). Surgeon reported attitudes of complete salpingectomy performance in general practice outside an academic setting was greater with a device than without (79.5 vs. 35.3%; p < 0.001).Conclusion Use of a bipolar electrocautery device improved operative times and surgeon satisfaction for salpingectomy at cesarean over standard suture ligation. Device use improved surgeon reported outcomes and may improve incorporation of complete salpingectomy at cesarean.Key Points
Keywords: cesarean delivery; electrocautery; opportunistic salpingectomy; sterilization